Penyempitan dan Perluasan Makna Wakamono Kotoba yang Berkaitan dengan Pandemi Covid-19 - Hafidhah Salsabila; Vera Yulianti (Universitas Gadjah Mada, 2021)
There is a phenomenon of semantic changes in language, not to mention in Japanese slang words (wakamono kotoba), which mostly are the narrowing and generalization of meaning. Consequently, the Japanese language learners face difficulties in understanding the context of the meaning, particularly terms occured in Covid-19 pandemic era. Therefore, the purpose of this study is to examine the trend of the semantic changes in wakamono kotoba related to the Covid-19 pandemic, especially in the form of the narrowing and generalization of meaning. The method of this study was the qualitative descriptive approach using content analysis. Data were collected from social media Twitter using the searching keywords related to the Covid-19 pandemic. The analysis of the data referred to the theory of semantic changes from Traugott. This study concluded that the tendencies of the narrowing and generalization of meaning in wakamono kotoba related to the Covid-19 pandemic, which includes terms regarding restrictions on outdoor activities and social interaction, reflecting efforts to prevent the spread of Covid-19.